Plasma Osteopontin Levels and Adverse Cardiovascular Outcomes in the PEACE Trial - Abdalrhim, Ahmed D.; Marroush, Tariq S.; Austin, Erin E.; Gersh, Bernard J.; Solak, Nusret; Rizvi, Syed A.; Bailey, Kent R.; Kullo, Iftikhar J. (PloS one, 2016)
Osteopontin (OPN) is a secreted glycophosphoprotein that has a role in inflammation, immune response and calcification. We hypothesized that plasma OPN levels are associated with adverse cardiovascular outcomes in patients with stable coronary artery disease (CAD) and preserved ejection fraction (EF) enrolled in the PEACE trial. We measured plasma OPN levels at baseline in 3567 CAD patients (mean age 64.5 ± 8.1 years, 81% men) by a sandwich chemiluminescent assay (coefficient of variation = 4.1%). OPN levels were natural log (Ln) transformed prior to analyses. We assessed whether Ln OPN levels were associated with the composite primary endpoint of cardiovascular death, non-fatal myocardial infarction and hospitalization for heart failure using multiple event multivariable Cox proportional hazards regression. Adjustment was performed for: (a) age and sex; (b) additional potential confounders; and (c) a parsimonious set of statistically significant 10 variates. During a median follow-up of 4.8 years, 416 adverse cardiovascular outcomes occurred in 366 patients. Ln OPN was significantly associated with the primary endpoint; HR (95% CI) = 1.56 (1.27, 1.92); P <0.001, and remained significant after adjustment for age and sex [1.31 (1.06, 1.61); P = 0.01] and after adjustment for relevant covariates [1.24 (1.01, 1.52); P = 0.04]. In a secondary analysis of the individual event types, Ln OPN was significantly associated with incident hospitalization for heart failure: HR (95% CI) = 2.04 (1.44, 2.89); P <0.001, even after adjustment for age, sex and additional relevant covariates. In conclusion, in patients with stable CAD and preserved EF on optimal medical therapy, plasma OPN levels were independently associated with the composite incident endpoint of adverse cardiovascular outcomes as well as incident hospitalization for heart failure.